Ovine gastrointestinal parasite burden and the impact of strategic anthelmintic treatment in community-based breeding sites in Ethiopia - Molla, Wassie; Moliso, Mesfin Mekonnen; Gizaw, Solomon; Nane, Tesfalem; Arke, Asrat; Ayele, Firdawok; Knight-Jones, Theodore (Frontiers in Veterinary Science, 2023)
In Ethiopia, small ruminants contribute significantly to the livelihoods and food security but productivity is low with high disease burden and essential endoparasite control is not widely practiced. The current study assessed worm burden and its control in three districts in Ethiopia. All sheep older than three months in nine villages were treated with en-masse with albendazole and triclabendazole twice a year from 2018 to 2021. Treatments were administered under field conditions by animal health workers. Pre-and post-treatment data were assessed looking at faecal egg presence/absence and faecal egg per gram (EPG) count. A total of 1928 and 735 sheep were examined before and after deworming respectively. Before treatment worms were detected in 54.4% (95% CI: 52.2-56.6) of sheep. Strongylid (30.4%) and Fasciola (18.2%) were the most frequently identified parasites. Animals living in wet mid-highland environments were more than 23 times more likely to have strongylid eggs in their feces and 5 times more likely to have eggs from any gastrointestinal tract (GIT) parasite detected, as compared to animals living in moist highland agro-ecology. Over the course of the 2018-2021 community intervention there was total elimination of animals with a high worm burden (EPG>1500), and elimination of a third of those with moderate infections. Mild infections remained, largely accounted for by strongylid, which remain at low levels in healthy sheep. However, there were signs of emerging drug resistance. Generally, sheep in smallholder systems in Ethiopia experience a needlessly large economic burden from GIT worms. Routine therapy reduces this burden but smart strategies are needed to limit the onset of drug resistance.